A Multiplier Approach to Power Generation for Remote Tropical Regions (Global Journal of Science Frontier Research, 2015)
Multiplier effects can be relevant for evaluating alternative ways of generating electricity, especially in remote regions, were the superior method might be different from the method that would be chosen in a location near transport hubs. Remote tropical regions often have easily gathered amounts of biomass, and they also have sufficient sunlight to make solar energy a competitive way of generating electricity. Remote tropical regions also have export revenues that are currently being used to import gasoline and diesel for small-scale portable generators. Recent innovations in biomass converters and solar panels make it possible for these regions to create local employment and save scarce foreign exchange, while generating electricity more cheaply. We discuss these alternatives and compute multiplier effects to arrive at promising result.
Keywords: evaluating alternative ways; biomass converters; compute multiplier effects